Cycle spokes and chain related injuries in children - emerging injuries in Malaysia - Mohd Yusof, Nazri; Zulkifly, Ahmad Hafiz; Aziz, Mohd Yusof; Khalid, Kamarul Ariffin; Che Ahmad, Aminudin (Malaysian Medical Association, 2005)
A descriptive prospective study of 16 children with injuries inflicted by bicycle spokes and chain was undertaken to identify the demographic profiles of such injuries. Aspects of preventive measures are proposed.